Pengaruh Tingkat Energi Microwave Sebagai Alat Desinfeksi Terhadap Perubahan Dimensi Dental Stone - Larasati, Hazrina, drg. Noor Hafida W, Sp.KG (2016)
Dental gypsum stone is a product that often used in dentistry to make molds and models. Dental stone particles have α-hemihydrate particels with denser and prismatic form. Dental stone has the risk of spreading pathogenic microorganism which would appeared from saliva when didnot carried out disinfection. Improper disinfection method can affect dimensional changes so the accuracy of the dental stone is reduced. This study purpose to determine the effect of microwave energy as a disinfection of dimensional changes of dental stone. The method used is cylindrical samples with diameter of 30 mm and height of 15 mm was made usingblue dental stone by Moldano, Germany for 24 pieces. The samples divided into four groups. Group I was the dental stone without any disinfection. Group II was the dental stone disinfected with 600 watts of microwave energy for 7 minutes. Group III was the dental stone disinfected with 800 watt of microwave energy for 7 minutes. Group IV is the dental stone disinfected with 1000 watts of microwave energy for 7 minutes. Measurement of dimensional change in the samples was done by electronic digital caliper. This research tested by using parametric statistical tests One Way Anova. The results obtained that there were significant differences between the changes in the dimensions of dental stone produced by the use of microwave energy levels as a disinfection (p<0,05). The higher level of microwave energy that used will increased changes dimensions of dental stone.